Studi Identifikasi Jenis-Jenis Pantun dalam Masyarakat Kaur Provinsi Bengkulu - Apriansah, Dedi; Muktadir, Abdul; Lusa, Herman (Jurnal PGSD, 2018)
This study aims to identify the Kaur language rhymes in accordance with the types of rhymes in the Kaur community of Bengkulu Province. The approach and type of research used are qualitative survey. The research location is Pengubaian Village, Gedung Sako II Village and Air Dingin Village, Bintuhan city, Kaur Selatan District, Kaur District. Subjects used as informants in the research are the chief of Kaur customary institutions in the village of Air Dingin, Community leaders Pengubaian villagers, and community leaders Gedung Sako II Village. Data collection techniques used in this study are interviews to informants and documentation. The document obtained were analyzed by data reduction, data display, and conclusion. Validity of document using extension of observation, improvement of persistence, triangulation of source and member check. Research results collected fifty-two rhyme Kaur language rhymes contained in the three villages. Fourteen rhymes from the village of Pengubaian, eighteen rhymes from the village of Gedung Sako II and twenty rhymes from the village of Air Dingin. Based on the results of identification can be concluded that, from fifty-two Kaur language rhymes, which is adapted to the types of rhymes obtained, namely: a puzzle rhymes, nine advice rhymes, eight affection rhymes, three spirit rhymes, two custom rhymes, Three religious rhymes, eight witty rhymes, eleven figurative rhymes, six romance rhymes and one proverb rhymes.